Unique kinetics of nicotinic acid-adenine dinucleotide phosphate (NAADP) binding enhance the sensitivity of NAADP receptors for their ligand. - Patel, S; Churchill, G; Galione, A (2000)
Nicotinic acid-adenine dinucleotide phosphate (NAADP) is a novel and potent Ca(2+)-mobilizing agent in sea urchin eggs and other cell types. Little is known, however, concerning the properties of the putative intracellular NAADP receptor. In the present study we have characterized NAADP binding sites in sea urchin egg homogenates. [(32)P]NAADP bound to a single class of high-affinity sites that were reversibly inhibited by NaCl but insensitive to pH and Ca(2+). Binding of [(32)P]NAADP was lost in preparations that did not mobilize Ca(2+) in response to NAADP, indicating that [(32)P]NAADP probably binds to a receptor mediating Ca(2+) mobilization. Addition of excess unlabelled NAADP, at various times after initiation of [(32)P]NAADP binding, did not result in displacement of bound [(32)P]NAADP. These data show that NAADP becomes irreversibly bound to its receptor immediately upon association. Accordingly, incubation of homogenates with low concentrations of NAADP resulted in maximal labelling of NAADP binding sites. This unique property renders NAADP receptors exquisitely sensitive to their ligand, thereby allowing detection of minute changes in NAADP levels.